Comparison of viral phenotype and inflammatory biomarker responses in acute HIV-1 subtype A and C infections - McInally, Samantha; Claiborne, Daniel T.; El-Badry, Elina; Xu, Rui; Qin, Qianhong; Ende, Zachary; Deymier, Martin J.; Rhodes, Jake W.; Gilmour, Jill; Kilembe, William; Karita, Etienne; Allen, Susan A.; et al. (Frontiers in Microbiology, 2025)
IntroductionHIV-1 subtype A and subtype C infections have different rates of clinical disease progression, with subtype C infected individuals in the IAVI Protocol C multisite acute infection cohort having a 60% faster CD4 loss compared to subtype A.MethodsIn order to investigate whether differences were due to the phenotype of the transmitted founder virus (TFV), or inflammatory cytokines and chemokines, known to drive pathogenesis, we PCR amplified, sequenced and constructed infectious molecular HIV-1 clones from the plasma of 30 acutely infected individuals in Rwanda and Zambia. We next compared the inflammatory plasma cytokine/chemokine profiles of individuals pre- and post-the estimated date of infection of 20 Rwandan individuals infected with subtype A and 34 Zambians infected with subtype C HIV-1.ResultsA comparison of the replicative capacity of 14 subtype A and 16 subtype C TFV showed that they had similar replicative capacity (RC) scores. Nevertheless, high TFV RC scores were linked to more rapid CD4+ T cell loss, and higher inflammatory cytokine levels irrespective of subtype. Multivariable analyses showed that individuals infected with subtype C exhibited a significant increase in the levels of eleven pro-inflammatory cytokines/chemokines after infection, while, in subtype A infections only six cytokines were significantly elevated postinfection. Despite these differences, at 3-months post infection, similar overall biomarker profiles were observed in individuals infected with subtype A or subtype C viruses, primarily due to higher pre-infection baseline biomarker levels in Rwanda. In the combined cohort, we found a highly significant association between faster CD4+ T cell decline and higher levels of ITAC (CXCL11), which in turn was linked to higher TFV RC.DiscussionOverall, the data presented here argue against TFV RC as the basis for different pathogenic outcomes in the subtypes A and C. Moreover, levels of inflammatory cytokines that might drive disease progression were similar during acute infection indicating that additional studies are required to understand the mechanism underlying differences in disease progression between the two subtypes. For both subtypes, high levels of ITAC during acute HIV-1 infection are linked to rapid disease progression.